From Eyeball to Exact: A Meta-Analysis of an Innovation in Episiotomy with Angle-Guiding Devices - Hakim, Surahman; Bimanugraha, Bimanugraha; Hadinata, Valencia; Mardhiyah, Tha’atam; Kadarusman, Adib Kamil Putra (RSUP Dr. Kariadi, 2026)
BACKGROUND: Episiotomy is a surgical incision performed to enlarge the vaginal outlet during childbirth, but an inaccurate mediolateral angle may increase the risk of obstetric anal sphincter injury (OASIS). SCOPE: This systematic review focused on randomized controlled trials evaluating dedicated angle-guiding devices for mediolateral episiotomy, including Episcissors-60, Episioguide, and the Episiometer. AIMS: To compare guided episiotomy devices with conventional eyeball technique in achieving appropriate episiotomy angles and reducing OASIS. METHOD: A systematic search of PubMed, ScienceDirect, and Wiley was conducted according to PRISMA 2020 principles. Eligible studies included women undergoing vaginal birth in whom a guided device was compared with conventional scissors or routine practice. The primary outcome was post-suture episiotomy angle. Secondary outcomes were OASIS incidence, incision characteristics, pain, practical limitations, and risk of bias. RESULT: Four randomized controlled trials involving 543 participants were included. Guided devices produced higher post-suture episiotomy angles than conventional technique (standardized mean difference 0.88, 95% CI 0.69-1.06; Z = 9.33; P<0.00001), slthough heterogeneity was substantial (I2=97%). Based on the pooled contingency table, OASIS was more frequent in the eyeball group than in guided group (OR 4.85, 95% CI 1.38-17.07; P-=0.0069) CONCLUSION: Angle-guiding devices may improve episiotomy angle accuracy and may reduce OASIS risk, but the evidence remains limited by few trials, sparse OASIS event, indirect comparisons between devices, and substantial heterogeneity.